2015
DOI: 10.1111/tra.12303
|View full text |Cite
|
Sign up to set email alerts
|

The Phosphoinositide‐Gated Lysosomal Ca2+ Channel, TRPML1, Is Required for Phagosome Maturation

Abstract: Macrophages internalize and sequester pathogens into a phagosome.Phagosomes then sequentially fuse with endosomes and lysosomes, converting into degradative phagolysosomes. Phagosome maturation is a complex process that requires regulators of the endosomal pathway including the phosphoinositide lipids. Phosphatidylinositol-3-phosphate and phosphatidylinositol-3,5-bisphosphate (PtdIns(3,5)P 2 ), which respectively control early endosomes and late endolysosomes, are both required for phagosome maturation. Inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
99
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(108 citation statements)
references
References 55 publications
9
99
0
Order By: Relevance
“…Interestingly, TRPML1 overexpression does not rescue vacuole shrinkage induced by mTOR inhibition, consistent with PIKfyve and mTORC1 controlling vacuolar shrinkage through separate pathways. While we find that PIKfyve is not required for the degradation of engulfed corpses, TRPML1 loss of function does slow corpse degradation (data not shown), similar to a recent report (Dayam et al, 2015), suggesting that TRPML1 has PIKfyve-independent upstream functions. Perhaps basal ion fluxes controlled by TRPML1 are generally required to maintain lysosome function and further TRPML1 activation by PIKfyve is required to support the shrinkage of macroendocytic vacuoles that harbor complex substrates undergoing degradation, which is predicted to alter their osmotic potential.…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, TRPML1 overexpression does not rescue vacuole shrinkage induced by mTOR inhibition, consistent with PIKfyve and mTORC1 controlling vacuolar shrinkage through separate pathways. While we find that PIKfyve is not required for the degradation of engulfed corpses, TRPML1 loss of function does slow corpse degradation (data not shown), similar to a recent report (Dayam et al, 2015), suggesting that TRPML1 has PIKfyve-independent upstream functions. Perhaps basal ion fluxes controlled by TRPML1 are generally required to maintain lysosome function and further TRPML1 activation by PIKfyve is required to support the shrinkage of macroendocytic vacuoles that harbor complex substrates undergoing degradation, which is predicted to alter their osmotic potential.…”
Section: Discussionsupporting
confidence: 91%
“…S5A). Instead, given that i) MCOLN1 releases lysosomal Ca 2+ during autophagy to activate the phosphatase calcineurin that then de-phosphorylates and activates TFEB [18] and ii) that phagosome maturation triggers a prolonged increase in cytosolic Ca 2+ in a MCOLN1-dependent manner [16], we postulated that MCOLN1 and Ca 2+ may be required for phagocytosis-dependent control of TFEB. To assess this, we first treated cells with BAPTA-AM to chelate Ca 2+ and showed that this significantly reduced TFEB-GFP nuclear accumulation after phagocytosis (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In part, PIKfyve is required for phagosome-lysosome fusion by stimulating MCOLN1/TRPML1 (herein MCOLN1), a lysosomal Ca 2+ channel that binds to PtdIns(3,5)P 2 to release lysosomal Ca 2+ and trigger membrane fusion [15,16]. Indeed, silencing of MCOLN1 trapped lysosomes and phagosomes in a futile, docked step [16]. Interestingly, phagocytosis caused a prolonged increase in cytosolic Ca 2+ that depended on MCOLN [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transient receptor potential mucolipin 1 (TRPML1) (10,(13)(14)(15) belongs to the large family of transient receptor potential ion channels that permeates Ca 2ϩ , Na ϩ , and other cations (10,(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). Mutations in TRPML1 gene lead to mucolipidosis type IV (ML4) disease, which is characterized with defects in membrane trafficking in the late endocytic pathway (10,29), enlarged lysosomes (10,29), and impaired lysosome biogenesis (30 -32).…”
mentioning
confidence: 99%